True Interest Cost in Municipal Bond Bidding: An Integer Programming Approach - Nauss, Robert M. (Management Science, 1986)
Over $47 billion of tax exempt debt issues were sold to the public in 1982. A portion of this total was offered to municipal bond underwriters under a competitive bidding system using the criterion of minimum true interest cost (internal rate of return). The TIC bidding problem may be formulated as a nonlinear integer program. We develop a linearization which is embedded in a special purpose integer linear branch and bound algorithm. Computational results for several actual bidding problems are presented.